2017
DOI: 10.1002/cncr.30527
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship after lower gastrointestinal cancer: Patient‐reported outcomes and planning for care

Abstract: For lower GI cancer survivors, it is feasible to obtain PROs from an Internet-based survivorship tool. Survivors report a wide spectrum of LLTEs, and these can be used to inform counseling at the time of diagnosis and to help anticipate and respond to disease-related and treatment-related sequelae during follow-up. The authors are among the first to report on PROs in anal cancer survivors. Further investigation on the impact of SCPs on health care communication and use is needed. Cancer 2017;123:1860-1868. © 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
(57 reference statements)
0
36
1
Order By: Relevance
“…The following validated measures were used to assess survivor-specific outcomes: 1) Rapid Assessment of Physical Activity (RAPA) (Topolski et al, 2006); 2) Starting the Conversation (STC) for diet behaviors (Frick et al, 2017); 3) Center for Epidemiological Studies-Depression Scale (CES-D) (Knight et al, 1997); 4) State Trait Anxiety Inventory (STAI) (Meyerhardt et al, 2016); 5) Self-Efficacy to Perform Self-Management Behaviors Scale (Hershman et al, 2014); and 6) Medical Outcomes Study – Short Form-36 (SF-36) for QOL (McHorney et al, 1993). Demographics data was obtained using a self-report tool and included Instrumental Activities of Daily Living (IADL) (Fillenbaum and Smyer, 1981; Siegel et al, 2014) and perceived social support (Medical Outcomes Study Social Support Survey) (Edwards et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The following validated measures were used to assess survivor-specific outcomes: 1) Rapid Assessment of Physical Activity (RAPA) (Topolski et al, 2006); 2) Starting the Conversation (STC) for diet behaviors (Frick et al, 2017); 3) Center for Epidemiological Studies-Depression Scale (CES-D) (Knight et al, 1997); 4) State Trait Anxiety Inventory (STAI) (Meyerhardt et al, 2016); 5) Self-Efficacy to Perform Self-Management Behaviors Scale (Hershman et al, 2014); and 6) Medical Outcomes Study – Short Form-36 (SF-36) for QOL (McHorney et al, 1993). Demographics data was obtained using a self-report tool and included Instrumental Activities of Daily Living (IADL) (Fillenbaum and Smyer, 1981; Siegel et al, 2014) and perceived social support (Medical Outcomes Study Social Support Survey) (Edwards et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we observed a more equitable representation of male and female survivors than in previous studies utilizing the OncoLink SCP tool, in which a female preponderance is typically reported (7,19,21,22). We hypothesized that this was likely due to inclusion of responses from both patients and proxies, with the latter party responding in place for a majority of male survivors.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, this number is lower than previous studies utilizing responses from the OncoLink SCP tool for other cancer sites (16)(17)(18)(19). As many pancreatic cancer patients are anticipated to live with incurable disease from time of diagnosis or to relapse soon after treatment, providers may defer provision of an SCP.…”
Section: Discussionmentioning
confidence: 91%
“…Fatigue is also a frequent problem among other groups of cancer survivors, for example prevalences of over 40 % are reported for survivors of colorectal cancer and lung cancer (18)(19)(20). However, the prevalence of chronic fatigue in these groups is unknown as the duration of the fatigue symptoms was not measured.…”
Section: Measurement and Prevalencementioning
confidence: 99%